(untitled) (Global Journal of Medical Research, 2013)
The effect of erectile dysfunction potentially interferes with men’s self esteem, confidence, relationship, and overall sense of well being. The problem is increasing in all segments of the sexually active male population and affects both men and his partner. In younger man increase is attributed to substance abuse, such as recreation drugs and alcohol. Middle aged men are affected by medical conditions such as diabetes, hypertension, sexual diseases, organ transplant, coronary artery bypass surgeries and cancer, or the therapy of these problems. The older population is living longer, fuller lives and expects to remain sexually active, regardless of any existing medical conditions. Stress factors associated with modern life styles are affecting men of all ages and contribute greatly to the overall causes of erectile failure. Early identification, behavior modification and increased therapeutic options may improve patient’s outcome. By improving the knowledge and therapeutic options, it may be possible to identify patients at risk of erectile dysfunction and thus to lead a normal healthy life.